The Effect of Self-Efficacy and Learning Innovation on Teacher Performance - Hambali, Hambali; Nurlaili, Nurlaili; Marzuki, Marzuki; Hayati, Hayati; Ashlan, Said (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
The reason for this research is to find out and analyze: (1) the effect of Self-efficacy on teacher performance, and (2) the effect of learning innovation on teacher performance. The research subjects were the teachers of the Madrasah Aliyah Negeri Medan City with a total sample of 298 people taken by means of stratified proportional random sampling, the data were analyzed using path analysis after calculating the correlation of all research variables in the form of a matrix. The results of the analysis of the effect of exogenous variables on endogenous variables in each substructure obtained (1) Self-efficacy has a positive effect on teacher performance by 0,121 (2) learning innovation has a positive effect on teacher performance by 0,177. The results of the study illustrate that (1) there is a positive direct influence of Self-efficacy on teacher performance by 12,1 %, and (2) there is a direct positive influence of learning innovation on teacher performance of 17,7%.